Toxicarioside O Inhibits Cell Proliferation and Epithelial-Mesenchymal Transition by Downregulation of Trop2 in Lung Cancer Cells - Zheng, Wu-Ping; Huang, Feng-Ying; Dai, Shu-Zhen; Wang, Jin-Yan; Lin, Ying-Ying; Sun, Yan; Tan, Guang-Hong; Huang, Yong-Hao (Frontiers in Oncology, 2021)
Toxicarioside O (TCO), a natural product derived from Antiaris toxicaria, has been identified to be a promising anticancer agent. In this study, we aimed to investigate the effect of TCO on the proliferation and epithelial-mesenchymal transition (EMT) of lung cancer cells and its molecular mechanisms. Here, we indicated that TCO inhibits the proliferation of lung cancer cells both in vitro and in vivo. Our results demonstrated that TCO induces apoptosis in lung cancer cells. Moreover, we found that TCO suppresses EMT program and inhibits cell migration in vitro. Mechanistically, TCO decreases the expression of trophoblast cell surface antigen 2 (Trop2), subsequent inhibition of the PI3K/Akt pathway and EMT program. Overexpression of Trop2 rescues TCO-induced inhibition of cell proliferation and EMT, indicating that Trop2 plays a critical role in TCO-induced antitumor activity in lung cancer cells. Taken together, our results demonstrate that TCO markedly inhibits cell proliferation and EMT in lung cancer cells and provides guidance for its drug development.